Care in hybrid bodyminds: Blurring the boundaries between care and maintenance - Pateraki, Marilena (Neusis, 2024)
The aim of this study is the examination of the issue of care of the implanted cyborg bodies. I will highlight the fact that, contrary to deterministic arguments, the under-the-skin conjunction of biological/mechanical elements, and the emergence of a new entity directed to the world in a hybrid manner, does not constitute a simple linear process that eliminates disabilities and chronic illnesses, rendering care practices and, more generally, human labor superfluous. On the contrary, this intervention involves complexities located within a wide array of practices and materialities, which unfold within multiple temporalities. Thus, the present study shows that the care of cyborg bodies is becoming more complicated rather than eliminated, while new vulnerabilities are emerging through the aforementioned conjunction, and the boundaries between care and maintenance becoming blurred. The research findings presented are based on a qualitative study I conducted following grounded theory methodology, informed by Science, Technology, Society (STS) studies, on deep brain stimulation (DBS) and its implementation in persons with Parkinson’s disease (PD) in Greece.